Quality of care in the free maternal healthcare era in sub-Saharan Africa: a scoping review of providers' and managers' perceptions - Monica Ansu-Mensah; Frederick Inkum Danquah; Vitalis Bawontuo; Peter Ansu-Mensah; Tahiru Mohammed; Roseline H. Udoh; Desmond Kuupiel (BMC, 2021)
Abstract Background Free maternal healthcare financing schemes play an essential role in the quality of services rendered to clients during antenatal care in sub-Saharan Africa (SSA). However, healthcare managers' and providers' perceptions of the healthcare financing scheme may influence the quality of care. This scoping review mapped evidence on managers' and providers' perspectives of free maternal healthcare and the quality of care in SSA. Methods We used Askey and O'Malley's framework as a guide to conduct this review. To address the research question, we searched PubMed, CINAHL through EBSCOhost, ScienceDirect, Web of Science, and Google Scholar with no date limitation to May 2019 using keywords, Boolean terms, and Medical Subject Heading terms to retrieve relevant articles. Both abstract and full articles screening were conducted independently by two reviewers using the inclusion and exclusion criteria as a guide. All significant data were extracted, organized into themes, and a summary of the findings reported narratively. Results In all, 15 out of 390 articles met the inclusion criteria. These 15 studies were conducted in nine countries. That is, Ghana (4), Kenya (3), and Nigeria (2), Burkina Faso (1), Burundi (1), Niger (1), Sierra Leone (1), Tanzania (1), and Uganda (1). Of the 15 included studies, 14 reported poor quality of maternal healthcare from managers' and providers' perspectives. Factors contributing to the perception of poor maternal healthcare included: late reimbursement of funds, heavy workload of providers, lack of essential drugs and stock-out of medical supplies, lack of policy definition, out-of-pocket payment, and inequitable distribution of staff. Conclusion This study established evidence of existing literature on the quality of care based on healthcare providers' and managers' perspectives though very limited. This study indicates healthcare providers and managers perceive the quality of maternal healthcare under the free financing policy as poor. Nonetheless, the free maternal care policy is very much needed towards achieving universal health, and all efforts to sustain and improve the quality of care under it must be encouraged. Therefore, more research is needed to better understand the impact of their perceived poor quality of care on maternal health outcomes.